A security network in PSI photoprotection: regulation of photosynthetic control, NPQ and O2 photoreduction by cyclic electron flow - Chaux, Frédéric; Peltier, Gilles; Johnson, Xenie (Frontiers in Plant Science, 2015)
Cyclic electron flow (CEF) around PSI regulates acceptor-side limitations and has multiple functions in the green alga, Chlamydomonas reinhardtii. Here we draw on recent and historic literature and concentrate on its role in Photosystem I (PSI) photoprotection, outlining causes and consequences of damage to PSI and CEF’s role as an avoidance mechanism. We outline two functions of CEF in PSI photoprotection that are both linked to luminal acidification: firstly, its action on Photosystem II with non-photochemical quenching and photosynthetic control and secondly, its action in poising the stroma to overcome acceptor-side limitation by rebalancing NADPH and ATP ratios for carbon fixation.